The Effects of Human Resource Competencies, Internal Controls, and Accrual Accounting on Financial Report Quality - Jamaluddin; Hakim Muttaqim (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Government financial reporting demands accountability and transparency, yet challenges persist in achieving high-quality financial statements. This study examines the influence of human resource competencies and internal control implementation on the adoption of accrual-based accounting and their impact on the quality of financial reporting information. It also investigates the mediating role of accrual-based accounting in these relationships. The research utilized a quantitative approach, collecting primary data through questionnaires from 206 respondents, including heads of subdivisions and financial officers across 103 work units. Path analysis was employed using Structural Equation Modeling to test the relationships. The findings indicate that human resource competencies and internal control implementation significantly enhance the adoption of accrual-based accounting, contributing 12.7% and 79.7%, respectively. Both factors directly improve the quality of financial reporting information, with coefficients of 0.492 and 0.282, respectively, while accrual-based accounting has a direct effect of 0.290. Accrual-based accounting partially mediates the effects of human resource competencies and internal controls on reporting quality. In conclusion, competent personnel, robust internal controls, and accrual-based accounting are essential for producing relevant, reliable, and comparable financial reports, emphasizing the need for integrated accounting practices in government agencies.